Trends in diagnostic characters of Snakes species (Squamata) in the first two decades of the 21st century. - Aquino, Juan; Lima, Ingrid Lima E [UNESP]; Costa, Fabiana Rodrigues; Nunes, Ivan [UNESP] (Magnolia Press, 2025)
The number of recognized reptile species globally exceeds 12.440. Half of them have been described after 1925, and only in the 21st century 1,920 reptiles were described, which is almost 25% of the currently valid herpetofauna species. Of all reptile diversity, more than 4,000 are snakes. This makes it essential to understand how they arose, so researching taxonomic informative characters is crucial. Considering this, the following work traces the history of the use of diagnostic characters in snakes descriptions during the first two decades of the 21st century. For this purpose, a list of 661 new species described between 2001 and 2020 were obtained through The Reptile Database. The survey revealed a strong tendency for some morphological traits to be the main choice for descriptions, as the most diagnostic characters were related to head scalation (21.10%), morphometry (17.68%), coloration (15.44%), body scalation (14.77%) and dentition characters (10%), which demonstrates that there is still a prevalence of morphological characters in the descriptions of new species. Despite this, it is possible to observe an increase in the use of molecular data, especially in the last decade, suggesting that new descriptions tend to use different sources of information in search of an integrative approach. Tracing this scenario can provide valuable insights for future works on the descriptions of new snake taxa.